Merefleksikan Demokrasi Indonesia Pascapemilu 2024 dari Kacamata Filsafat Politik Jonathan Floyd - Solosumantro, Heribertus; Leba, Adolfus (Indonesian Character Journal, 2025)
This paper aims to critically reflect on the development of democracy in Indonesia through the lens of Jonathan Floyd’s Political Philosophy. The background of this paper is the attitudes and policies of political elites and oligarchs in Indonesia, particularly in the context of the 2024 General Elections, which deviate from the 1945 Indonesian Constitution and Pancasila as the guiding principles of Indonesian communal life. The author questions the political attitudes and understanding of the political elite, which tend to undermine democratic life among grassroots communities in Indonesia—such as the stipulation of the age limit for presidential and vice-presidential candidates in Article 67 of Law No. 7 of 2017 and the selective process in political party membership. The method used in this paper is qualitative research. The findings and discussion are presented in four parts. First, the author describes the history of democracy in Indonesia from the Reform Era to the present. Second, the author explains the current political situation in the context of Indonesia’s 2024 elections. Third, the author analyses Jonathan Floyd’s Political Philosophy. Fourth, the author applies Jonathan Floyd’s Political Philosophy as a critical tool to reflect on recent democratic practices in Indonesia. Through these four areas of discussion, the author offers recommendations for a political model that should be embraced in the context of post-2024 election democracy in Indonesia.